Comparison of branched, fenestrated, and parallel strategies for endovascular treatment of thoracoabdominal aortic pathologies involving visceral regions - Ma, Xiaochen; Wu, Zhishi; Zhu, Guanglang; Guo, Mingjin; Li, Yongxin; Liu, Junjun; Liu, Mingyuan; Li, Youjin; Ye, Bo; Chen, Tao; Qi, Ming; Xiao, Hongyan; et al. (Frontiers in Cardiovascular Medicine, 2024)
Purpose To compare the long-term efficacy of the parallel stent graft (PSG), fenestrated stent graft (FSG), and branched stent graft (BSG) techniques to treat thoracoabdominal aortic pathologies. Materials and methods In total, 291 patients with thoracic aortic aneurysm (TAA) and dissection (TAD) involving visceral arteries who underwent PSG (n = 85; 15 TAA and 70 TAD), FSG (n = 107; 47 TAD and 60 TAA), or BSG (n = 99; 37 TAD and 62 TAA) were included from multiple centers from January 2015 to December 2022, and a total of 1,108 visceral aortic branches were reconstructed. Results The average reconstruction time of each visceral aortic branch for FSG, BSG, and PSG is 27.5 ± 12.1, 23.2 ± 11.9, and 18.8 ± 11.8 min, respectively (P < 0.01). The free-from-endoleak rate at the last follow-up for FSG, BSG, and PSG was 86.9%, 91.9%, and 60.0%, respectively. The last follow-up patency rate for FSG, BSG, and PSG was 85.0%, 91.9%, and 94.1%, respectively. The average reconstruction price of each visceral aortic branch for FSG, BSG, and PSG was 41.40 ± 3.22 thousand RMB, 41.84 ± 3.86 thousand RMB, and 42.35 ± 4.52 thousand RMB, respectively (P = 0.24). Conclusion To treat the aortic pathologies involving the visceral segment, BSG had a lower endoleak rate and higher branch patency rate when compared with the FSG and PSG techniques. The expense of BSG was comparable to the other two techniques.